Estudio de factibilidad para la creación de un Meliponario comunitario que fomente el desarrollo del turismo científico en el sector El Placer de la parroquia Río Verde en el Cantón Baños de Agua Santa - Chicaisa Guallichico, Ruth Nicole (2022)
The Cerro Candelaria Natural Preserve, located in the Llanganates-Sangay corridor, has a highly biodiverse and sensitive ecosystem that is threatened by the anthropogenic activities of the population settled in the buffer zone in addition to the lack of adequate tourism planning. For this reason, the objective of this research work was to determine, through a feasibility study, the viability of investment for the implementation of a community (beehive) meliponarium (living museum of native bees) in the village of El Placer in the Río Verde Parish. Based on the qualitative and quantitative analysis of the tourism market, and through surveys made to a population sample that allowed identifying the tourist profile and market consumption trends. In addition, interviews were made to determine the supply, acknowledging direct and indirect competition. The results enabled creating the branding and products related to the project. In the second objective, a technical study was implemented to identify the physical, technical and engineering conditions needed for the project through the interpretation of georeferencing maps, evaluation tables and 3D design plans, defining the optimal location and resources required for its construction. In addition to anticipating the actions for the prevention, mitigation and remediation of the environmental impacts that it could produce. The third objective was the legal management study, in order to describe the organizational framework that would manage the process of the community meliponarium (beehive), as well as defining the corresponding legal structure. Finally, the economic and financial study of the revenue and expenses of the project was executed, applying calculation of NPV, IRR and C/B values to analyze the economic feasibility of the investment. Based on the studies performed, it is estimated that its implementation and subsequent operation will positively contribute to the local development of the community and shift the economic activities by promoting sustainable tourism and research, through the strengthening of the organizations formed in the study site, Caserío el Placer